1993
DOI: 10.1128/mcb.13.8.4648
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a high-affinity interaction between v-Crk and tyrosine-phosphorylated paxillin in CT10-transformed fibroblasts.

Abstract: The genome of avian sarcoma virus CT1O encodes a fusion protein in which viral Gag sequences are fused to cellular Crk sequences containing primarily Src homology 2 (SH2) and Src homology 3 (SH3) domains. Transformation of chicken embryo fibroblasts (CEF) with the Gag-Crk fusion protein results in the elevation of tyrosine phosphorylation on specific cellular proteins with molecular weights of 130,000, 110,000, and 70,000 (p130, p110, and p70, respectively), an event which has been correlated with cell transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
199
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(206 citation statements)
references
References 47 publications
5
199
2
Order By: Relevance
“…This is supported by the observation that the presence of Pyk2 in CrkL immunoprecipitates or in Crk-SH2 in vitro co-precipitation experiments mirrors the pattern of tyrosine phosphorylated paxillin (Figures 2 and 4). Tyrosine phosphorylated paxillin is known to be a binding partner for the SH2 domain of CrkL-related proteins, 43,59 and is also found in a complex with Pyk2. 46 PMA-induced megakaryocytic differentiation of K562 cells is dependent on the activity of the MEK/MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by the observation that the presence of Pyk2 in CrkL immunoprecipitates or in Crk-SH2 in vitro co-precipitation experiments mirrors the pattern of tyrosine phosphorylated paxillin (Figures 2 and 4). Tyrosine phosphorylated paxillin is known to be a binding partner for the SH2 domain of CrkL-related proteins, 43,59 and is also found in a complex with Pyk2. 46 PMA-induced megakaryocytic differentiation of K562 cells is dependent on the activity of the MEK/MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that members of the CrkL family bind to phosphorylated paxillin. 43 The PMA-mediated events that take place upon stimulation of K562 cells lead to the expression of megakaryocyte markers. 8 Therefore, it was of interest to determine whether the expression of Pyk2, a tyrosine kinase expressed in megakaryocytes, 44,45 was regulated by PMA.…”
Section: Differentiation-dependent and -Independent Effects Of Pma Onmentioning
confidence: 99%
“…The abnormalities in lung cancer may also re¯ect changes in the cytoskeleton and cytoskeleton associated proteins. Previously, it has been shown that transforming oncogenes such as v-src (Brown and Cooper, 1996), v-crk (Birge et al, 1993), BCR/ABL , and E6 (bovine and human papilloma virus) (Tong and Howley, 1997) interact with the cytoskeleton in oncogenesis. It is therefore possible that the various molecular abnormalities in lung cancer also contribute to transformation via the cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…Paxillin is tyrosine phosphorylated in response to oncogenes such as v-src (Schaller and Parsons, 1994), v-crk (Birge et al, 1993) and BCR/ABL (Salgia et al, 1995a). This focal adhesion protein is tyrosine phosphorylated in response to growth factors such as PDGF/EGF (Rankin et al, 1996), IL-3 and steel factor (Salgia et al, 1995b), and neuropeptides such as bombesin (Charlesworth et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, enormous progress in our understanding of signal transduction has emerged from studies on Crk. The canonical signaling pathway, defined by recognition of specific phosphotyrosine motifs by the SH2 domain (in the context of p-Tyr.X.X.Pro) [4] and Polyproline Type II motifs by the N-terminal SH3 domain {in the context of Pro. X. X.…”
mentioning
confidence: 99%